1984
DOI: 10.1136/bmj.288.6416.518
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole and generation of oxygen radicals by monocytes: potential role in immunosuppression.

Abstract: A study was conducted investigating the possibility that the immunosuppressive action of methimazole (the active metabolite of the antithyroid drug carbimazole) might be due to an effect on the production of oxygen radicals by monocytes. Techniques comprised measurement of luminol dependent chemoluminescence in monocytes and a spectrophotometric assay for production of hydrogen peroxide.The results showed definite inhibition of formation of oxygen radicals by resting and stimulated monocytes, which may explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 10 publications
1
33
0
1
Order By: Relevance
“…Immune complexes associated with complement deposition have been observed on the thyroid follicular basement membrane (Werner et al, 1972;Kalderon & Bogaars, 1977) and the terminal component of complement, C9, has been detected at this site, implying formation of the membrane attack complex (MAC) of complement (Oleesky et al, 1986). We recently confirmed this by immunohistochemical staining of terminal complement complexes (TCC) around the thyroid follicles in Graves' disease and Hashimoto's thyroiditis, but not in normal glands (Weetman et al, 1989). Serum TCC concentrations were also elevated in these conditions and decreased with treatment of Graves' disease.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Immune complexes associated with complement deposition have been observed on the thyroid follicular basement membrane (Werner et al, 1972;Kalderon & Bogaars, 1977) and the terminal component of complement, C9, has been detected at this site, implying formation of the membrane attack complex (MAC) of complement (Oleesky et al, 1986). We recently confirmed this by immunohistochemical staining of terminal complement complexes (TCC) around the thyroid follicles in Graves' disease and Hashimoto's thyroiditis, but not in normal glands (Weetman et al, 1989). Serum TCC concentrations were also elevated in these conditions and decreased with treatment of Graves' disease.…”
Section: Introductionsupporting
confidence: 64%
“…We have previously shown that TCC were elevated in the serum of patients with Hashimoto's thyroiditis and Graves' disease and decreased with anti-thyroid drug treatment (Weetman et al, 1989). TCC antigens were also detected immunohistochemically along the follicular basement membrane in autoimmune but not normal thyroid glands.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, depending on the degree of NADPH oxidase enzyme complex activity, a superoxide anion (O -2 ) is formed. An important factor determining the immunosuppressive action of thionamides, including methimazole, is the inhibition of the respiratory burst in resting monocytes and following their stimulation with PMA (38). In the study, no significant differences in the spontaneous NBT reduction test (modified RBA test) between groups C and E were found, although the stimulation with PMA, an activator of the free radical function, showed a lower oxygen activity of peripheral blood neutrophils in the group treated chronically with methimazole.…”
Section: Resultsmentioning
confidence: 52%
“…This suggests that oxidative alteration ofthe thyroid may play a role early in the development of the disease. Although increased free radical production in OS thyroids containing normal amounts ofiodine has yet to be demonstrated, thionamide drugs have been shown to decrease free radical formation (25)(26)(27). However, while this may explain the action of PTU, the effect of aminotriazole, a catalase inhibitor, cannot be explained by this mechanism.…”
Section: Discussionmentioning
confidence: 80%